The Amazing Language of Medicine : Understanding Medical Terms and Their Backstories - Taylor, Robert B. (Springer International Publishing : Imprint: Springer, 2017)
This book tells the intriguing and often colorful stories of the medical words we use. The origins of clinical and scientific terms can be found in Greek and Latin myths, in places such as jungles of Uganda and the islands of the Aegean Sea, in the names of medicine's giants such as Hippocrates and Osler, and in some truly unlikely sources. In this book you will learn the answers to questions such as: - What disease was named for an American space flight? - Do you know the echoic word for elephantine rumbling of the bowels? - What drug name was determined by drawing chemists' notes out of a hat? - What are surfer's eye, clam digger's itch, and hide porter's disease? This book can give you new insights into the terms we use every day in the clinic, hospital, and laboratory. Knowing a word's history assists in understanding not only what it means, but also some of the connotative subtleties of terms used in diagnosis and treatment. The Amazing Language of Medicine is intended for the enrichment of physicians, other health professionals, students, and anyone involved in clinical care and medical science.
Keywords: Medicine.; General practice (Medicine).; Primary care (Medicine).; Medicine -- History.; elektronické knihy; electronic books